2022
DOI: 10.3390/ijms231911538
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Rhizobia Nodulating Anthyllis vulneraria L. from Ultramafic Soil as Plant Growth Promoting Bacteria Alleviating Nickel Stress in Arabidopsis thaliana L.

Abstract: Rhizobia, which enter into symbiosis with legumes, can also interact with non-legumes and promote plant growth. In this paper, we explored the effects of nickel (Ni, 200 µM) on Arabidopsis thaliana (Col-0) inoculated with plant growth-promoting (PGP) rhizobia nodulating ultramafic Anthyllis vulneraria. The isolated PGP strains tolerant to Ni were identified as Rhizobium sp. and Bradyrhizobium sp. The isolates highly differed in their PGP abilities and Ni resistance. Without Ni-stress, the plants inoculated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 85 publications
(233 reference statements)
0
0
0
Order By: Relevance
“…•− generation rate, respectively, compared to the control. Reduced activity of APX, SOD, and CAT and an elevated H 2 O 2 content was observed in Arabidopsis thaliana in Ni-polluted soil [59]. In another study, Valivand et al [54] reported that Ni-polluted soil reduced antioxidant enzyme activities (CAT and POD) and increased the contents of H 2 O 2 and MDA in the zucchini plant.…”
Section: Defense System Of Salixmentioning
confidence: 96%
See 1 more Smart Citation
“…•− generation rate, respectively, compared to the control. Reduced activity of APX, SOD, and CAT and an elevated H 2 O 2 content was observed in Arabidopsis thaliana in Ni-polluted soil [59]. In another study, Valivand et al [54] reported that Ni-polluted soil reduced antioxidant enzyme activities (CAT and POD) and increased the contents of H 2 O 2 and MDA in the zucchini plant.…”
Section: Defense System Of Salixmentioning
confidence: 96%
“…Nickel reduces plant growth and yield by reducing the absorption of nutrients by the roots, damaging thylakoid structures, lowering ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) activity, and affecting stomatal closure and the biosynthesis of chlorophyll [57,58]. Interestingly, adding PGPR to Ni-polluted soil notably boosted the growth and the DW of Arabidopsis thaliana L. [59]. The contents of phenolic compounds in wheat [56], while that of protein and carotenoid in Zea mays [60] were boosted in the presence of Bacillus sp.…”
Section: Agronomical and Biochemical Traitsmentioning
confidence: 99%